Unsteady pressure measurements around rotor of an axial flow fan under stable and unstable operating conditions - Shin, YH; Kim, KH; Kang, CS (JAPAN SOC MECHANICAL ENGINEERS, 2005)
This study presents some measurement results on the unsteady pressure fields around rotor under stable and unstable operating conditions of an axial flow fan. The unsteady static pressure of rotor passage was measured by using high frequency pressure transducers mounted on the casing wall. The measurements on the unsteady total pressure at rotor inlet and outlet were also conducted with specially designed high frequency total pressure probe. Double Phase-Locked Ensemble Averaging Technique was used for analysis of pressure fluctuations around the rotor at rotating stall onset point. From the results, the unsteady pressure fields during stable and unstable operations of the axial fan were investigated and compared with each other. Particularly one period of rotating stall could be divided into two regions, stalled flow and unstalled flow region respectively. Furthermore the former could be also classified into two zones, bubbled and disturbed region by their features. The flow characteristics for each zone were described in detail and the static and total pressure fields were also analyzed in terms of the pressure distribution along pressure side and suction side on the blade tip profile.